A crise do trabalho na cafeicultura de vitória da conquista - Bahia - Santana, Aurelane Alves (2016)
We seek in this research to understand the historical background of the coffee workers and the changes that result from the complex production of capital restructuring in the field, which, in the Planalto da Conquista, was consolidated in this start of century, representing a large discard of work force of the coffee productive process. In the context of structural unemployment, we seek to identify the most cruel effects of the restructuring process in the conditions of present life of workers that experience the unbridled growth of precarious work, rare and temporary, which intensifies the difficulties of social reproduction of the working class. In this sense, we discussed about the complexities that affect the coffee labor universe, based on the recent changes in the production because of the intensive use of machines in the fields, which has led to the elimination of many jobs and created a mass of unemployed workers, essential for capitalist accumulation. Thus, what we see in the field of study area is the formation of a contingent of superfluous workers willing to work, but can no longer to enter in the work in coffee plantations or in other labor activities, experiencing chronic unemployment or submission to degrading labor and slave labor in the few farms that still employ human labor. In this text are discussions about the contradictions in the richness production that are based fundamentally on the exploration, precariousness and derealization of workers.